Passive sampling for pesticides and PAHs in the SIMONA project - Mörtl Mária (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
Passive samplers (solid phase extraction, SPE disks and Polar Organic Chemical Integrative Sampler, POCIS) were tested to monitor 85 pesticides (including glyphosate and aminomethylphosphonic acid, AMPA), 19 polycyclicaromatic hydrocarbons (PAH) components, metals in the Drava river. Among pesticides the time weighted average concentrations of terbuthylazine, S-metolachlor and tebuconazole were the highest. Some chlorophenoxy acids (2,4-D, mecoprop-P and MCPA) also appeared at lower levels. Bentazone, DEET and diuron were detected in all samples at low levels. Among the 19 PAHs phenanthrene occurred at the highest concentrations, but fluoranthene, pyrene and naphthalenes also contributed to the total PAH concentration. In the case of the POCIS sampler selective for glyphosate and AMPA, the levels of AMPA metabolite exceeded significantly that of the parent herbicide compound.